(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the use of mobile technologies in geography education, highlighting mobile learning, its opportunities, and conveniences. It outlines the advantages of utilizing mobile technologies, emphasizing their significant practical importance. The article also recommends several methods for creating electronic educational resources based on mobile technologies and ways to use mobile devices for educational purposes.